HUBUNGAN ANTARA PEMANTUAN GLUKOSA DARAH MANDIRI DENGAN HIPOGLIKEMIA PADA DIABETES MELLITUS TIPE 2 DI PUSKESMAS KEBUN JERUK - Dewi, Ratna (Indonesian Journal of Nursing Health Science, 2016)
Abstract Hypoglycemia, or low blood glucose results when too much insulin is comparable with the available glucose in the blood. This causes blood glucose levels dropped to less than 70 mg / dl. The aim of research to determine the relationship of self-monitoring of blood glucose with hypoglycemia in type 2 diabetes mellitus descriptive analytic method with cross sectional approach, sample size 91, chi-square test statistic. The results of the study most of the clients do not perform blood sugar checks as many as 62 people (68.1%). The results of statistical tests of blood glucose self-monitoring relationship with hypoglycemia had a significant relationship to the client type 2 diabetes mellitus in Puskesmas Kebun Jeruk. P value of 0.000, p <Î± (0.05). Conclusion there is relationship with the self-monitoring of blood glucose hypoglycemia in type 2 diabetes mellitus is recommended for patients with type 2 diabetes mellitus monitoring of blood sugar levels is very important because it helps the proper medical treatment, thereby reducing the risk of severe complications.Keywords: blood glucose self-monitoring, hypoglycemia, diabetes mellitus type 2